2020
DOI: 10.1111/aor.13786
|View full text |Cite
|
Sign up to set email alerts
|

The absorbing filter Oxiris in severe coronavirus disease 2019 patients: A case series

Abstract: Objective Hypercytokines cause acute respiratory distress syndrome (ARDS) in COVID‐19 patients, which is the main reason for ICU treatment and the leading cause of death in COVID‐19 patients. Cytokine storm is a critical factor in the development of ARDS. This study evaluated the efficacy and safety of Oxiris filter in the treatment of COVID‐19 patients. Materials and Methods Five patients with COVID‐19 who received CRRT in Henan provincial people's hospital between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 18 publications
0
40
0
1
Order By: Relevance
“…A recent case series showed improvement in COVID-19 patients’ haemodynamics and organ function following CRRT with oXiris filter. 7 Another study also demonstrated the safety of CRRT with oXiris filter in COVID-19 patients with reduction in CRP, IL-6 and PCT levels. However, there is still insufficient evidence on the optimum timing and indication for initiation of CRRT with oXiris filter in order to achieve the best outcome.…”
Section: Discussionmentioning
confidence: 92%
“…A recent case series showed improvement in COVID-19 patients’ haemodynamics and organ function following CRRT with oXiris filter. 7 Another study also demonstrated the safety of CRRT with oXiris filter in COVID-19 patients with reduction in CRP, IL-6 and PCT levels. However, there is still insufficient evidence on the optimum timing and indication for initiation of CRRT with oXiris filter in order to achieve the best outcome.…”
Section: Discussionmentioning
confidence: 92%
“…We and others have explored the use of cytokine blood purification in an attempt to prevent, control, or reduce (suspected) hyperinflammation [ 27 , 28 , 29 , 30 , 31 ]. Several blood purification devices are currently on the market, showing a significant reduction of pro-inflammatory cytokines and restore homoeostatic dysregulation associated with systemic inflammatory syndromes [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed 19 cases (43.2%) ( We and others have explored the use of cytokine blood purification in an attempt to prevent, control or reduce (suspected) hyperinflammation [26][27][28][29][30]. Several blood-purification devices are currently on the market, showing a significant reduction of pro-inflammatory cytokines and restore homeostatic dysregulation associated with systemic inflammatory syndromes [31][32][33].…”
Section: Time-series Analyses Of Inflammatory Biomarkers Vital Signsmentioning
confidence: 99%